Disentangling the trend in the warming of urban areas into global and local factors. Issue 1 (16th September 2021) - Estrada, Francisco; Perron, Pierre
Abstract: Large cities account for a significant share of national population and wealth, and exert high pressure on local and regional resources, exacerbating socioenvironmental risks. The replacement of natural landscapes with higher heat capacity materials because of urbanization and anthropogenic waste heat are some of the factors contributing to local climate change caused by the urban heat island (UHI) effect. Because of synergistic effects, local climate change can exacerbate the impacts of global warming in cities. Disentangling the contributions to warming in cities from global and local drivers can help to understand their relative importance and guide local adaptation policies. The canopy UHI intensity is commonly approximated by the difference between temperatures within cities and the surrounding areas. We present a complementary approach that applies the concept of common trends to extract the global contributions to observed warming in cities and to obtain a residual warming trend caused by local and regional factors. Once the effects of global drivers are removed, common features appear in cities' temperatures in the eastern part of the United States. Most cities experienced higher warming than that attributable to global climate change, and some shared a period of rapid warming during urban sprawl in the mid‐20th century in the United States. Abstract : Disentangling the contributions to warming in cities from global and local drivers can help to understand their relative importance and guide local adaptation policies. We present an approach that applies the concept of common trends to extract the global contributions to observed warming in cities and to obtain a residual warming trend caused by local and regional factors. Once the effects of global drivers are removed, common features appear in cities' temperatures in the eastern part of the United States.